Effects of energy drinks on mental health and academic performance of university students: A systematic review and meta-analysis protocol. - Danyla Rafaela Oliveira Batista; Kaio Vinicius C Silva; Miguel Torres; Woska Pires da Costa; Manuel Monfort-Pañego; Priscilla Rayanne E Silva; Matias Noll (PLoS ONE)
Objectives Energy drink (ED) consumption is frequently observed among higher education students and is often associated with increased concentration and academic performance. However, the purported benefits are not fully supported by scientific evidence. This protocol details methods for a systematic review and meta-analysis to evaluate the effects of ED on university students' mental health and academic performance. Methods The PECO framework will guide the search strategy, and the protocol will follow the PRISMA-P 2015, PRESS 2015, and PRISMA-S guidelines. The searches will be conducted in the following databases: Web of Science, Scopus, Ovid, PubMed, Embase, FSTA, CINAHL, and SPORTDiscus. The GRADE recommendations and the Downs and Black scale will assess study quality and bias. All statistical analyses will be conducted using Comprehensive Meta-analysis software. We will use Cochran's Q with p < 0.05 to indicate significant heterogeneity and I² to quantify heterogeneity between studies. The Trim and Fill technique and Egger's regression test will be applied to evaluate the funnel plot that will be generated. Results Carrying out the systematic review proposed by this protocol will provide evidence on the short-, medium-, and long-term effects of ED use on academic performance and mental health among higher education students. Conclusion A deeper understanding of ED consumption among higher education students can inform the development of evidence-based educational and public health policies to promote student well-being and mitigate associated health risks. Register on prospero CRD42024580044.